2021
DOI: 10.1093/ije/dyab050
|View full text |Cite
|
Sign up to set email alerts
|

Analyses of ‘change scores’ do not estimate causal effects in observational data

Abstract: Background In longitudinal data, it is common to create ‘change scores’ by subtracting measurements taken at baseline from those taken at follow-up, and then to analyse the resulting ‘change’ as the outcome variable. In observational data, this approach can produce misleading causal-effect estimates. The present article uses directed acyclic graphs (DAGs) and simple simulations to provide an accessible explanation for why change scores do not estimate causal effects in observational data. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
71
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(75 citation statements)
references
References 20 publications
0
71
0
Order By: Relevance
“…Effect estimates show the difference in risk for each outcome comparing those with the highest compared with least mental health symptoms. Because interpretation of within-person change scores can be problematic (Tennant, Arnold, Ellison, & Gilthorpe, 2021 ), main analyses examined associations between mental health and health behaviours at each timepoint; however, change score analyses are provided as additional analyses. Regression analyses were carried out by cohort and results were meta-analysed to formally assess heterogeneity using the I 2 statistic and obtain pooled estimates of association.…”
Section: Methodsmentioning
confidence: 99%
“…Effect estimates show the difference in risk for each outcome comparing those with the highest compared with least mental health symptoms. Because interpretation of within-person change scores can be problematic (Tennant, Arnold, Ellison, & Gilthorpe, 2021 ), main analyses examined associations between mental health and health behaviours at each timepoint; however, change score analyses are provided as additional analyses. Regression analyses were carried out by cohort and results were meta-analysed to formally assess heterogeneity using the I 2 statistic and obtain pooled estimates of association.…”
Section: Methodsmentioning
confidence: 99%
“…The baseline difference in EQ-5D VAS for the 12-month follow-up data set, while statistically significant was small and not clinically relevant. Because any association between our proposed predictor of response (duration of pain) and baseline pain is important in the context of casual inference, 29,30 we used an equivalence testing approach to verify the lack of association in our data. 31 The largest mean difference in pain ratings (0-10 scale) between pain duration groups <3 months and ≥12 months was found to be 0.3 units, equating to a standardised mean difference of 0.15.…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that an association between the proposed baseline predictor of response and the baseline value used in the calculation of change can bias inferences. 30 We found no association between the duration, and degree of pain at baseline (Supplementary Tables B, http://links.lww.com/BRS/B657 and C, http://links.lww.com/BRS/B657), and both baseline duration and status were entered into our statistical modal in an attempt to quantify independently adjusted influences. Nevertheless, we highlight the fact that our study was not a randomised controlled trial and so robust inferences about causality cannot be made.…”
Section: Discussionmentioning
confidence: 97%
“…Among the published IPD-MA of NRSs in which continuous outcomes were assessed at baseline and follow-up (61% published since 2018), the change score was the most common statistical method, followed by ANCOVA—an unexpected finding because Cochrane recommends using ANCOVA to incorporate baseline outcome data in meta-analysis ( 45 ). A recent published paper by Tennant et al also recommends not to use change score in studies that aim to estimate a causal-effect because their results are not meaningful unless the baseline exposure and baseline outcome are independent from each other, which is extremely unlikely in non-randomized studies ( 46 ). However, Tennant et al also highlighted that adjustment for the baseline outcome, such as in ANCOVA, should not be made when the baseline outcome plausibly occurs after the exposure.…”
Section: Discussionmentioning
confidence: 99%